Implementation of Solar Energy Technology for Public Street Lighting in Kampung Karag: Implementasi Teknologi Energi Surya pada Penerangan Jalan Umum di Kampung Karag - Aldy Yansah; Oky Supriadi; Luki Utomo; Arya Putra Sidiq; Muhammad Wahyu Taqwana (JATI EMAS (Jurnal Aplikasi Teknik dan Pengabdian Masyarakat), 2026)
The main problem faced by Karag Village, Kadudodol, Cimanuk District, Pandeglang, Banten, is the lack of lighting facilities at night. This results in a decreased sense of security, limited mobility, and an increased risk of accidents. This community service activity aims to improve the quality of street lighting in Karag Village. The activity was carried out by installing solar-powered Public Street Lighting (PJU). The service activity also included technical education for the community regarding the use and maintenance of renewable energy systems. Through field surveys, determining installation points, installing components, and technical training, this activity resulted in several solar panel PJU units that can automatically turn on for several hours each night. Monitoring results showed that the system worked stably, the solar panels were able to charge the batteries properly, and the LED (Light Emitting Diode) lamps provided adequate light intensity for the needs of village roads. In addition to technical results, this activity also increased community understanding about how to maintain solar panels, check battery conditions, and maintain the safety of simple electrical installations. Community participation in the installation process also strengthened a sense of ownership of the facilities built. Overall, this activity succeeded in providing a real solution to the limited lighting and encouraged increased community capacity in managing renewable energy technology independently and sustainably.